Desenvolvimento de uma ferramenta móvel para vistoria de imóveis - Vieira, Cleber dos Santos (2013)
The real estate sector in Brazil has shown high growth rates in recent years, but the tools that assist in the process of acquisition or lease of real estate are quite scarce. With the popularity of smartphones and tablets and to minimize and identify potential problems in real estate, this project presents a solution developed for the Android operating system that will assist in carrying out the inspection of a property. From the registry of a property, it is possible by means of checks patterns registered in the user application perform inspection of a property without any additional configuration.